2017
DOI: 10.3389/fnana.2017.00051
|View full text |Cite
|
Sign up to set email alerts
|

Reticular Formation and Pain: The Past and the Future

Abstract: The involvement of the reticular formation (RF) in the transmission and modulation of nociceptive information has been extensively studied. The brainstem RF contains several areas which are targeted by spinal cord afferents conveying nociceptive input. The arrival of nociceptive input to the RF may trigger alert reactions which generate a protective/defense reaction to pain. RF neurons located at the medulla oblongata and targeted by ascending nociceptive information are also involved in the control of vital f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 135 publications
(191 reference statements)
3
77
0
4
Order By: Relevance
“…In this study, we aimed to investigate whether experimental pain responses in older individuals correlate with FA of the white matter tracts between the prefrontal cortex and the periaqueductal gray (PAG), located in the brainstem. The PAG has direct anatomical connections with the prefrontal cortex [38] and sends neuronal input to key components of the descending pain modulatory system, including the rostroventromedial medulla, caudal ventrolateral medulla, and dorsal reticular nucleus [39]. Stein et al (2012) have demonstrated that FA of the white matter tracts connecting the prefrontal cortex with the PAG correlates with placebo analgesia [40].…”
Section: Probabilistic Tractography Of White Mattermentioning
confidence: 99%
“…In this study, we aimed to investigate whether experimental pain responses in older individuals correlate with FA of the white matter tracts between the prefrontal cortex and the periaqueductal gray (PAG), located in the brainstem. The PAG has direct anatomical connections with the prefrontal cortex [38] and sends neuronal input to key components of the descending pain modulatory system, including the rostroventromedial medulla, caudal ventrolateral medulla, and dorsal reticular nucleus [39]. Stein et al (2012) have demonstrated that FA of the white matter tracts connecting the prefrontal cortex with the PAG correlates with placebo analgesia [40].…”
Section: Probabilistic Tractography Of White Mattermentioning
confidence: 99%
“…The PAG is proposed to function as the gateway for pain control from higher brain centres to the spinal cord (Close, Cetas, Heinricher, & Selden, ; Martins & Tavares, ; Silva, Costa‐Pereira, Martins, & Tavares, ). The PAG does not project directly to the spinal cord but uses a relay located at the rostral ventromedial medulla (RVM).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, using CFA-induced chronic inflammatory pain model, Hu et al (27) found a strong activity of the NR2B subunit of NMDAR that was selectively upregulated in the PAG. RVM is an intermediate in PAG to modulate pain as this region is a crucial integrated relay in the descending modulation of pain (27,68,69). The activation of ON cells in RVM results in the facilitation of nociceptive transmission while the stimulation of OFF cells mediates the inhibition of nociceptive processing (69).…”
Section: Central Sensitisation During Ramentioning
confidence: 99%